The Influence of Individual Motivation on Employee Performance at Tanah Grogot Ward Office - Muhammad Akbar; M. Yunus Syam (International Journal of Asian Business and Management, 2023)
Development planning in the Ward area cannot be separated from the implementation of the Ward Government which is the leading unit in providing services to the community and is a strategic milestone in the success of all development programs. The type of research used in this research is quantitative research. The population in this study were employees, totaling 35 employees, all of whom were samples. From the results of multiple linear regression analysis, we get the function equation Y = 2.224+0.119X1+0.141X2+0.245X3. The regression coefficient (R), which describes the strong relationship between the independent variables and the dependent variable can be seen in the test, which is equal to 0.734. This means that there is a strong relationship between the independent variable and the dependent variable. Fcount value ˃ Ftable or 12.088 ˃ 2.9113 and probability value 0.000 ˂ 0.05. Shows that individual motivation variables have a simultaneous (together) effect on employee performance. Of the individual motivational variables, the variable need for achievement gives a dominant influence, this is evidenced by the value of tcount ˃ ttable or 3.521 ˃ 1.6955 and the smallest probability value is 0.001 ˂ 0.05. Seeing the results of the discussion above, it is concluded that the initial hypothesis proposed is accepted, because the initial hypothesis states that the dominant variable is the variable need for achievement (X1)